2008
DOI: 10.1016/j.jpcs.2008.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Free standing double walled boron nanotubes

Abstract: Based on density functional calculations we propose stable structures of free standing double walled boron nanotubes in the form of two single walled boron nanotubes inside one another.Puckering of the boron sheets allows the inner atoms of the outer wall and outer atoms of the inner wall to be matched giving sp-type hybrid σ bonding between the walls. The structural stability, in the case of double walled tubes, increases as the bond interaction between the walls strengthens.All the optimized structures repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…The existence of quasi-planar [7] and tubular [8] boron clusters was predicted theoretically and confirmed more recently experimentally [9,10]. In addition, double-walled boron nanotubes were predicted to be highly stable [11]. These authors found that the interaction between the walls in form of σ-bonds increases the stability of the system in opposite to the carbon nanotubes where the walls are connected by Van-der-Waals forces only, in which no chemical bonds are formed among the neighboring walls.…”
Section: Introductionsupporting
confidence: 60%
“…The existence of quasi-planar [7] and tubular [8] boron clusters was predicted theoretically and confirmed more recently experimentally [9,10]. In addition, double-walled boron nanotubes were predicted to be highly stable [11]. These authors found that the interaction between the walls in form of σ-bonds increases the stability of the system in opposite to the carbon nanotubes where the walls are connected by Van-der-Waals forces only, in which no chemical bonds are formed among the neighboring walls.…”
Section: Introductionsupporting
confidence: 60%
“…While at least 16 forms of boron (some of which were probably impurity-stabilized) have been reported, the existence as pure polymorphs of boron has been established for the α rhombohedral, β rhombohedral, two tetragonal phases, and the recently discovered orthorhombic highpressure partially ionic γ phase [2]. Boron has been investigated both theoretically and experimentally as bulk boron, nanotubes, clusters, quasi planar, monolayer, and bilayer sheets [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Novel boron nanobelts or nanowires have been successfully synthesized [13,14], and experimentally shown to be semimetals or narrow-gap semiconductors, but the exact atomic structures are still not fully resolved [14].…”
mentioning
confidence: 99%
“…An even more stable modification of β-boron has been proposed with 106 atoms in the unit cell 5 . Boron based nanostructures have also been proposed 6 , and boron single and double wall nanotubes and boron nanoribbons have been reported [7][8][9] .…”
mentioning
confidence: 99%